An ultra-low chronology of Iron Age Palestine - Hagens, Graham
The dating of the complex historical events of Palestine, Syria and Egypt during the Iron Age have long occupied scholarly research. Here, a new scheme of dating is offered, which may help to remove gaps and anomalies in the sequence.